Risk management in civil construction: the contractor's perceptions - Schocair, Marilia Medeiros; Silva, Rodrigo Oliveira da; Amaral, Marcelo Gonçalves do; Barra, Geraldo Magela Jardim; Silveira, Rebecca Impelizieri Moura da (Revista de Administração da UFSM, 2023)
Purpose: This study seeks to understand how the managers of the civil construction industry perceive risk management in their projects and businesses based on a case study in the region of Volta Redonda-RJ. Design/methodology/approach: Primary data was collected through questionnaires and interviews. The primary quantitative data were analyzed using Paraconsistent Logic and presented with descriptive statistics. Findings: It was found that 87% of the sample did not go through any steps of the risk management process. For those that did, the steps were essentially intuitive and informal. Further, a distortion was observed on behalf of the managers regarding the understanding of what risk management is, what it is helpful for, and the difference between their projects and the business itself. Practical implications: Although not generalizable, the research results show a high appetite for risk on the part of contractors but a low willingness to absorb its effects. Originality/value: Studies that apply paraconsistent logic to understand builders' perceptions of the importance of risk management are scarce in the literature. Also, there is little literature about the management aspects of this industry.